Nilai Edukatif Q.S Al-Mumtahanah Ayat 7-9 Tentang Toleransi (Kajian Ilmu Pendidikan Islam) - Abdillah, Syaik; Jum'ah, Nasrul (MASAGI : Jurnal Pendidikan Agama Islam, 2022)
In Islam, Prophet Muhammad (peace be upon him) is the foremost exemplar in religious life, renowned for his high tolerance towards those with differing and opposing beliefs. This study is motivated by the lack of awareness regarding intolerant behavior towards differing beliefs, which leads to discrimination and radicalism in Indonesia. Consequently, the research aims to offer an understanding of Islamic Education Science as outlined in Surah Al-Mumtahanah verses 7-9 concerning tolerance. The objectives of this study are to describe: (1) the educational values of Surah Al-Mumtahanah verses 7-9 related to tolerance, and (2) the educational values within these verses from the perspective of Islamic Education Science. The research employs a descriptive analysis methodology, specifically through a library research approach. The technique utilized is content analysis, drawing on primary sources such as the Quran and secondary sources including books, journals, and tafsir (Islamic exegesis). The findings of this study reveal two key educational values about tolerance in Surah Al-Mumtahanah: the importance of compassion between Muslims and non-Muslims, and the necessity of acting justly and benevolently towards both Muslim and non-Muslim communities. Keywords: Educational Values, Tolerance, Islamic Education Science